The Relationship between Workplace Friendship and Workplace Well Being on Productivity - Imaduddin Imaduddin (Newinera Publisher, 2024)
The purpose of this research is to determine the variables of Workplace Friendship and Workplace Wellbeing on Employee Productivity. This type of research includes quantitative research. This research is survey research. The population in this study were employees at the Pasar Makassar Raya Regional Public Company. With a sample size of 124 people, the data collection technique uses a questionnaire that has been prepared to answer the hypothesis. The research results found that Workplace Friendship and Workplace well-being simultaneously had a positive and significant effect on employee productivity.